Participatory Survey Data Analysis as Catalyst for Empowering Youth as School Health Change Agents. Issue 4 (July 2019) - Garnett, Bernice; Beattie, Helen; Koller, Sharon; Moore, Mika; Scott, Karen; Maseroni, Michelle; Holmes, Breena
Addressing and preventing the major health issues affecting American adolescents requires collaborative and authentic youth participation. Our current time reflects a pendulum shift toward authentic youth voice and democratic participation in school wellness and reform. In this application article, we outline and describe a youth–adult partnership curriculum to engage youth as change agents in their school community through youth-led research activities with publicly available and locally derived data from the Youth Risk Behavior Surveillance Survey. Getting to "Y": Youth Bring Meaning to the Youth Risk Behavior Survey (GTY) is a positive youth development/youth participatory action research initiative, whereby students analyze their school health data and use those data as a starting point to create change in their school community. Focus groups were conducted with GTY youth and adult alumni in spring 2018. Results from the focus group data reinforce the GTY core assumptions and speak to the importance of structured opportunities for youth agency. GTY is a scalable, developmentally appropriate, resource-efficient, and empirically based curriculum that provides structured opportunities for youth-led research utilizing local Youth Risk Behavior Surveillance Survey data as a youth–adult partnership model to increase youth agency and engagement with school/community health needs.